Longitudinal study of personal adjustment and social conditions in the Fort McMurray area Vol I: Research design ... - Ltd., Earl Berger (University of Alberta Library, 1978)
The purpose of Phase 1 was to establish a research design for a longitudinal study to identify and explain the relationships between social and personal adjustment of people in the oil sands region. The research design was to be implemented in Fort McMurray and to be applicable to any resource community. The Study Team examined the literature and studies reievant to resource communities and conventional communities, and consulted with the Client and interested departments. The purposes of this review were to determine the central dimensions of personal, family, social, economic and community life to be identified and monitored during the Longitudinal Study; the data and information required; the most appropriate theoretical and methodological approaches to take; and the instruments to monitor and measure change. The Study Team's emphasis was upon user requirements; theoretical and conceptual soundness; and feasibility within the time and resources available. This work was integrated with a comparable study ...